The Role of Organizational Justice and Social Capital on Job Satisfaction and Organizational Commitment: Notes and Review - Agus Maliana (Budapest International Research and Critics University, 2022)
Organizational justice is a very important aspect in human resource management and is also a topic that is widely discussed in various management literature. One of the interesting studies related to organizational justice is the research by Tjahjono et al. (2019) regarding the role of organizational justice which consists of distributive justice and procedural justice in increasing organizational satisfaction and commitment as well as the moderating effect of social capital on higher education institutions. This study aims to review and provide notes on the research by Tjahjono et al. (2019) which is uploaded to Int. J. Business Excellence, 17(3), 336-360. This study is qualitative research with a literature review method. The results show that there are several notes related to the research of Tjahjono et al (2019) which are grouped into three aspects, namely conceptual, method and development of research results. Future studies are important to conduct a more in-depth and broader review related to organizational justice and social capital both in the education industry and other industries.